Mangrove Forest Bioecology in Dasun Village, Lasem Sub-district, Rembang Regency, Central Java - Utami, Dela R.; Roziaty, Efri (Jurnal Biologi Papua, 2025)
Mangrove are one of the biotic components that form ecosystems in coastal areas. They are flowering plants with a tree habit that are highly tolerant of elevated salt levels. Mangrove ecosystems serve as habitats for various species of flora and fauna, and are therefore known for their high bioecological diversity. This study aims to analyze the bioecology of the mangrove ecosystem in Dasun Village, Lasem Sub-district, Rembang Regency, Central Java. The research method used was a survey with the transect line technique. Sampling of mangrove vegetation was conducted using square plots measuring 20 × 20 m, while fauna sampling was conducted within a 10-meter radius of the vegetation plots. All flora and fauna found within the plots were recorded as bioecological data of the mangrove ecosystem. Sampling was conducted in three different locations within the mangrove ecosystem area of Dasun Village. The results revealed three families of mangrove flora: Primulaceae (9 species), Combretaceae (5 species), and Rhizophoraceae (171 individuals). The mangrove fauna identified consisted of eight families from the class Gastropoda, two families from the class Malacostraca, and one family each from the classes Pisces, Aves, and Mammalia. Abiotic factors such as temperature, humidity, pH, and salinity were also measured. Temperature ranged from 29.3-33.8 °C, humidity from 68-73%, pH from 6.8-6.9, and salinity from 0.2-0.5 ppt. These results indicate that the mangrove ecosystem in Dasun Village supports a diverse range of mangrove flora and fauna, demonstrating its bioecological richness